Thermo-poroelastic analysis of drilling fluid pressure and temperature on wellbore stresses in the Mansouri oilfield, SW Iran - Alireza Pirhadi; Pooria Kianoush; Shahab Varkouhi; Reza Shirinabadi; Adel Shirazy; Aref Shirazi; Arash Ebrahimabadi (Results in Earth Sciences)
Ensuring wellbore stability is essential for successful oilfield drilling operations, as instability can prolong drilling time and escalate costs, potentially resulting in halted operations and loss of wells. This study presents a comprehensive thermo-poroelastic analysis of wellbore stability, focusing on the impact of thermal effects and pore pressure dynamics in shale formations. Utilizing a coupled thermo-poroelastic model, the research investigates the influence of varying drilling fluid pressure and temperature on wellbore stresses in the Bangestan Reservoir in SW Iran. The analysis employs Hoek-Brown's law, continuity equation, Darcy's law, compatibility equation, and thermal relations, solved using the finite element method within a complex geological model. The findings reveal that horizontal wells are more stable than other configurations, with a pressure limit of 57.23 MPa required to maintain stability. Additionally, a 55–60° azimuth demonstrates the highest mud limit among horizontal wells, while a 20° contrast is observed between formation temperature and drilling fluid in the optimal azimuth. This research introduces innovative methodologies that integrate thermal and pore pressure effects, significantly enhancing the understanding of wellbore stability and contributing to safer and more efficient drilling operations.